Fayyaz Lahiji And A Different Reading of lbn Sina's Theory of Imprinted Forms - MahmoudReza Mohajeri; Azizullah Afshar Kermani (حکمت سینوی, 2021)
God’s prior knowledge of the creatures, before their creation, is one of the most complex topics of God’s attributes in theology, which various opinions have been expressed about it, one of the most famous of which is Ibn Sina’s inverted forms. In this article, we aim to review Lahiji's different readings of the theory. Lahiji first accepts the famous reading of Ibn Sina’s imprinted forms. According to this theory, God Almighty precedes the creation of objects by imprinted forms that are based on the divine Essence and the essentials of the essence. But this theory was criticized by many Islamic philosophers and theologians after Ibn Sina. Therefore, Lahiji raised objections by presenting a different reading of the theory of imprinted forms to get rid of the drawbacks. He believes that 'Ilm-i Ijmālī (collective knowledge) is the same as Ilm-i Tafṣīlī (detailed knowledge). And their differentiation is due to the analysis of the human mind; whereas the knowledge of God is being the same as the Divine Essence in terms of simplicity and oneness. Due to the fact, therefore, the different reading of the scholar Lahiji is getting close to Mullah Sadra's theory expressing God’s eternal knowledge of the creatures is collective as well as detailed.